AKIBAT HUKUM KREDIT TANPA JAMINAN BAGI PIHAK DEBITUR - Novina Pratiwi Putheri, Ni Made; Bela Siki Layang, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
Assurance of the debtor is an absolute requirement for the purpose of legal certainty which is expressly set out in the credit agreement. This is because insurance is very important for the bank to counter the risks that might arise in the future as a result of the granting of credit by the bank to the borrower.Legal consequences in case of unsecured credit unsecured credit defaults that contain greater risk that the legal consequences that all the wealth effect debtor either moving or not moving the existing and will exist in the future, a guarantee of fulfillment of all of the debt payments. In the banking institutions in general, apply the precautionary principle in any extension of credit to borrowers by asking insurance known as credit or collateral, in an effort to minimize the risk of loss that would be suffered as a result of the debtor can not pay off the loan in accordance with the agreed in the credit agreement.
Keywords: Unsecured Loans, Debtor